Innovation Behavior Research: Global Trends and Emerging Themes in Entrepreneurial Business Practices - Chakim, Mochamad Heru Riza; Utami, Rahayu Tri; Sitanggang, Tantri Wenny; Tanjung, Azrul; Rizky, Agung; Beldiq, Eiser Aaron (Aptisi Transactions On Technopreneurship (ATT), 2024)
Innovation behavior research has emerged as a critical field due to its role in enhancing business competitiveness and organizational performance. This bibliometric analysis aims to provide a comprehensive understanding of global trends and emerging themes in innovation behavior research from 2015 to 2024. Using the Dimensions database, 11,798 articles were identified and analyzed with VOSviewer software. The results reveal that Australia, China, the United Kingdom, and the United States are the top contributors to this research, with strong international collaboration networks highlighting its global nature. Brock University, Jiangsu University, and Erasmus University Rotterdam stand out for their collaborative networks and strategic research directions. In the author-based analysis, research efforts primarily focus on the relationship between entrepreneurial orientation, transformational leadership, and innovation behavior. Frontiers in Psychology and Sustainability emerge as influential journals, covering topics such as digital transformation, organizational behavior, and sustainable business practices. Groundbreaking studies have developed frameworks linking innovation behavior with knowledge sharing, digital transformation, and conflict management. Keyword co-occurrence analysis highlights "innovation", "performance", and "leadership" as frequently occurring terms, reflecting a core focus on understanding how innovation directly impacts organizational outcomes and the importance of transformational leadership in fostering innovation behavior. The findings provide valuable insights into global innovation behavior research, identifying emerging interdisciplinary themes like digital transformation and sustainability. Future research should explore global collaboration networks, interdisciplinary approaches, and the influence of leadership styles on innovation behavior.